Adropin treatment restores cardiac glucose oxidation in pre-diabetic obese mice. (April 2019) - Thapa, Dharendra; Xie, Bingxian; Zhang, Manling; Stoner, Michael W.; Manning, Janet R.; Huckestein, Brydie R.; Edmunds, Lia R.; Mullett, Steven J.; McTiernan, Charles F.; Wendell, Stacy G.; Jurczak, Michael J.; Scott, Iain
Abstract: Exposure to a high fat (HF) diet promotes increased fatty acid uptake, fatty acid oxidation and lipid accumulation in the heart. These maladaptive changes impact cellular energy metabolism and may promote the development of cardiac dysfunction. Attempts to increase cardiac glucose utilization have been proposed as a way to reverse cardiomyopathy in obese and diabetic individuals. Adropin is a nutrient-regulated metabolic hormone shown to promote glucose oxidation over fatty acid oxidation in skeletal muscle homogenates in vitro . The focus of the current study was to investigate whether adropin can regulate substrate metabolism in the heart following prolonged exposure to a HF diet in vivo . Mice on a long-term HF diet received serial intraperitoneal injections of vehicle or adropin over three days. Cardiac glucose oxidation was significantly reduced in HF animals, which was rescued by acute adropin treatment. Significant decreases in cardiac pyruvate dehydrogenase activity were observed in HF animals, which were also reversed by adropin treatment. In contrast to previous studies, this change was unrelated to Pdk4 expression, which remained elevated in both vehicle- and adropin-treated HF mice. Instead, we show that adropin modulated the expression of the mitochondrial acetyltransferase enzyme GCN5L1, which altered the acetylation status and activity of fuel metabolism enzymes to favor glucose utilization. Our findings indicate that adropin exposure leads to increased cardiac glucose oxidation under HF conditions, and may provide a future therapeutic avenue in the treatment of diabetic cardiomyopathy. Graphical abstract: Unlabelled Image Highlights: Long-term exposure to a high fat diet can promote metabolic dysfunction in the heart. Adropin is a nutrient-responsive hormone shown to restore glucose oxidation in the skeletal muscle of diabetic mice. We show that acute treatment of high fat diet-induced obese mice with adropin restores cardiac glucose oxidation in vivo . Adropin improves pyruvate dehydrogenase activity in obese mice, which is linked to reduced inhibitory lysine acetylation.